Clinical validation of controlled exposure to birch pollen in the Environmental Exposure Unit (EEU). Issue 1 (December 2016) - Ellis, Anne; Soliman, Mena; Steacy, Lisa; Adams, Daniel; Hobsbawn, Barnaby; Walker, Terry
Abstract Background The Environmental Exposure Unit (EEU) in Kingston, Ontario, Canada is a controlled allergen challenge facility (CACF) that has been previously clinically validated for the use of ragweed and grass pollen in clinical studies. In this study we aim to validate the use of birch pollen to challenge allergic participants. Methods A total of 59 volunteers were screened and 38 birch allergic participants and ten non-allergics completed the study, outside of tree pollen season. Participants had to have a minimum of 2-year history of allergic rhinoconjunctivitis during the typical tree pollen season and have a positive skin prick test to birch allergen ≥5 mm from the control. Qualified participants were exposed to birch (Betula pendula ) pollen for 4 h in the EEU and recorded their symptoms of sneezing, rhinorrhea, nasal congestion, nasal itch which comprised the total nasal symptom score (TNSS), as well as itchy/watery eyes, red/burning eyes and itching of ears/palate/throat which along with the TNSS comprised the total rhinoconjunctival symptom score (TRSS) along with Peak Nasal Inspiratory Flow (PNIF) at baseline and at 30 min intervals for the duration of exposure, then hourly for up to 12 h from the start of exposure. Results Allergic participants reported a gradual rise in TNSS and TRSS, reaching a mean and standard error of the mean of 7.08 ± 0.45 and 11.58 ± 0.93 respectively by 180 min from the start of exposure. Symptoms gradually declined to near baseline values following departing from the unit, reaching 1.9 and 2.7 by 450 min. Allergic participants reported significantly higher TNSS than non-allergics starting from 30 min (p < 0.01, two-way ANOVA with Bonferroni corrections), maintaining maximum significance from 60 to 300 min (p < 0.0001) and losing significance by 420 min. TRSS and PNIF followed similar trends as those seen with TNSS. Participants were phenotyped using previously published definitions using the TNSS into Early Phase Responders (EPR, 57.8 %), protracted EPR (pEPR, 39.5 %), and Dual Phase Responders (DPR, 2.7 %). Conclusions The EEU can competently challenge birch allergic participants and achieve statistically significant changes in symptoms and nasal airflow, while such changes are not reported in non-allergic controls. Trial registration NCT02351830 clinicaltrials.gov